Leadership Style Analysis PT. Bangun Persada Regatama During the Covid 19 Pandemic - Widya Rahayu; Komang Satria Wibawa Putra (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
To break the chain of spread of the Covid-19 virus, the government issued a PPKM policy which requires essential companies to only employ 25% of their employees, this has resulted in the company experiencing an unexpected crisis. the readiness of a company's leadership to determine the level of effectiveness in dealing with the onslaught of the Covid-19 pandemic. This analysis focuses on the leadership style in the company PT. BPR in dealing with the Covid-19 outbreak by examining the level of alertness, responsiveness, cohesiveness, and coordination between organizations. The results of the study show that leaders at PT BPR use an empathetic leadership style which is one of the choices for leaders to carry out leadership functions during the covid-19 pandemic. One of Rensis Likert's theories is 4 Systems or 4 Leadership communication styles. A leader must have the attitude of a Consultative Leader, meaning that with the current covid-19 pandemic, the leader should have little trust in his subordinates, subordinates need information, ideas or opinions through consultation. Because applying an empathetic leadership style alone is not enough to maintain the company and only reduces employee performance because it is considered that leaders provide opportunities and employees will be in a comfort zone.